WEB SERIES OLAH NALAR (Perancangan Kampanye Sosial Seputar Isu Remaja Indonesia) - Aditya Utama (DeKaVe, 2014)
Olah Nalar is a social campaign trying to engage Indonesian youth to think more critically, smartly, andrationally in dealing with social issues that exist in their surrounding. The concepts that will be realized in this creationare divided into three parts, each of which represents three different social issues, namely: fanaticism, technologicaldeterminism, and violent behavior.The format of these works is using communication campaign format and choosing web series as a medium platform.Simply put, web series is chosen because it is considered capable of accommodating the needs of the creator; from thecommunication aspect, the freedom of creativity, as well as the financial considerations.In the process, these works try to present the aspects of novelty in the persuasion area by performing some experimentssuch as the use of soft persuasion style in the delivery of the message, relying on the aspects of logic as the foundationfor the credibility of the message, and the use of visual closing at the end of each video.Hopefully, the logical perspectives that are contained in the video are able to provide new awareness that can organizethe perspective and behavior of the adolescent to become a better person individually and socially.